Bee-ing successful: generating sustainable income through Meliponini Edu Park / Grace Flavyeliz Sinong ... [et al.] - Sinong, Grace Flavyeliz; Jasni, Nur Aziemah; Fitri Said, Rozlianah; Sisa, Mohd Hafezan; Shuaib, Dayang Shurtinie (Universiti Teknologi MARA, Kedah, 2024)
This business proposal outlines the establishment of Meliponini Edu Park for the Meliponini Club, Faculty of Plantation and Agrotechnology (FPA), Universiti Teknologi MARA Sabah Branch (UiTMCSH). The Meliponini Club, comprised of FPA students, will manage the project, focusing on generating income through stingless bee farming. The project focuses on promoting education on stingless bees among students and communities and encouraging students with agropreneurship skills to create sustainable revenue. The fundraising projects offer premium quality stingless bee products, promoting stingless bee education and sustainable practices. It offers unique selling propositions such as sustainable stingless bee farms, the production of stingless bee-based products, and diverse educational opportunities. The target customers of this project include students and staff of UiTMCSH, communities, and visitors. The project fosters a self-sustaining model that benefits the students and faculty.